Applying a co-designed medication plan for safer medication treatment in older persons: a feasibility study - Malin Holmqvist; Axel Ros; Johan Thor; Linda Johansson (Pilot and Feasibility Studies)
Abstract Background To promote patient safety, international guidelines highlight the importance of a joint plan for continued treatment in older persons. Accordingly, in a co-design initiative involving older persons and healthcare professionals, a medication plan was developed. This study aimed to assess the feasibility of applying the medication plan for older persons in primary care. The objectives were to examine the feasibility of the medication plan in clinical practice and to examine the feasibility of methods that could be used to study a broader implementation. Methods A prospective study design, using both qualitative and quantitative methods, was employed. During appointments at primary care centres, physicians (n = 6), persons aged 75 or older (n = 21), and, when applicable, their next of kin (n = 2) collaboratively agreed on a medication plan, which was documented in the electronic health record. Over a 3-month follow-up period, data regarding the feasibility of the medication plan (usability and fidelity) and the feasibility of the research methods (recruitment and retention rates, data collection, and outcome measures) were collected. Results Usability assessed by the System Usability Scale scored a median of 51.3 out of 100 for physicians. The participants’ experiences of the medication plan’s usability addressed functionalities, individualisation for relevance, resources, and a de-prioritised medication plan. Fidelity was assessed based on 8 out of 15 older persons reporting that they had received a medication plan, and 59% of all prescribed medications had documented goals and/or comments. The recruitment rate was 75% for physicians and 70% for older persons. There were no changes in polypharmacy and no contact with healthcare due to suspected adverse drug events. The participants’ perceptions of the medication plan’s ability to promote patient safety addressed awareness and information, challenges beyond the medication plan, and patient involvement. Conclusions The implementation of the co-designed medication plan encountered challenges related to usability and fidelity, requiring collaborative refinements of the prototype. Additional difficulties arose from using a low-fidelity prototype in clinical practice. Our results emphasise the strength of combining qualitative and quantitative methods to capture participants’ perspectives on the medication plan’s ability to promote patient safety. Before conducting a larger study, the evaluation methods require further refinement. Trial registration. ClinicalTrials.gov NCT06016140 (retrospectively registered).